Study the pathological and Residual Toxic effect of Malathion in Mice Nervous System - Mohammed, Soad Abdulkareem (The Iraqi Journal of Veterinary Medicine, 2008)
In present experiment , study was done on the pathological and residual effect of malathion in mice 50 white mice randomly divided into 3 group : 1st group including (20)mice was given single oral dose .1.5 ppm in drinking water 2nd group contain (20) mice given single dose 1.5 ppm malathion orally in drinking water and repeated the same dose at 2nd and 3rd week i.e (three repeated doses), the 3rd group (10) mice act as control group .The long of experiment was 60 days , the following parameter were done . 1- Clinical Signs: treated group 1st and 2nd groups showed nausea and diarrhea 2- Pathological changes : 1st and 2nd group showed lesion which were more significant in 2nd group .Pathological changes characterized by neuron necrosis , Brain odema , and mononuclear cell present with spinal cord damage . 3- Residual investigation: which were more significant in 2nd group at 60 days of treatment, the Malathion residual reach 0.90 ppm in brain and spinal cord.